Maternal Healthcare Providers in Uttar Pradesh, India: How to Position Informal Practitioners within the System? - Chesta Sharma; Kanchan Mukherjee (Tehran University of Medical Sciences, 2014)
Objective: To understand the knowledge and services of informal providers and to explore their role in addressing the human resource gap in Uttar Pradesh, India, within the context of maternal health. Materials and methods: The study is exploratory in nature, conducted in four blocks of four districts of Uttar Pradesh state, India. Semi-structured interviews were conducted with 114 informal providers. Results: More than one-third (38%) providers have some formal education and unrecognized degrees. Approximately three-fourths (74%) of them have more than 5 years of work experience. They also provide delivery and in-patient services and have basic equipment available. However, they lack essential knowledge about maternal health. They have mixed opinion about their contribution towards maternal health but the only ones available. Therefore, despite lacking requisite knowledge, training and services, they become indispensable due to lack of emergency and timely public health services, and being the only ones existing in the community. Conclusion: Informal sector practitioners are a critical link in reaching out to population for health services in developing countries. As opposed to the general notion, they possess years of formal education, experience, informal trainings along with trust of communities. Thus, it becomes important to accept their presence and manage them to the best of their abilities even for specialized care like maternal health.